Krill Oil Alleviated Methamphetamine-Induced Memory Impairment via the MAPK Signaling Pathway and Dopaminergic Synapse Pathway - Ru, Qin; Tian, Xiang; Xiong, Qi; Xu, Congyue; Chen, Lin; Wu, Yuxiang (Frontiers in Pharmacology, 2021)
Methamphetamine (METH) abuse exerts severe harmful effects in multiple organs, especially the brain, and can induce cognitive dysfunction and memory deficits in humans. Krill oil is rich of polyunsaturated fatty acids, while its effect on METH induced cognitive impairment and mental disorders and underlying mechanism remain unknown. The aim of present study was to investigate the protective effect of krill oil on METH-induced memory deficits and to explore the molecular mechanisms by using integrated strategy of bioinformatics analysis and experimental verification. METH exposed mice were treated with or without krill oil. Learning and memory functions were evaluated by Morris water maze. The drug-component-target network was constructed combined the network pharmacology. The predict hub genes and pathways were validated by serum biochemical detection and western blot. With krill oil treatment, memory impairment was significantly improved. 210 predicted targets constituted drug-compound-target network by network pharmacology analysis. 20 hub genes like DRD2, MAPK3, CREB, BDNF, Caspase-3 were filtered out as the underlying mechanisms of krill oil on improving memory deficits induced by METH. The KEGG pathway and GO enrichment analyses showed that the MAPK signaling pathway, cAMP signaling pathway, and dopaminergic synapse pathways were involved in the neuroprotective effects of krill oil. In the hippocampus, DRD2, cleaved caspase-3, γ-H2AX expression levels were significantly increased in the METH group but decreased in the krill oil-treated group. Meanwhile, krill oil enhanced the expressions of p-PKA, p-ERK1/2, p-CREB. Our findings suggested that krill oil improved METH-induced memory deficits, and this effect may occur via the MAPK signaling pathway and dopaminergic synapse pathways. The combination of network pharmacology approaches with experimental validation may offer a useful tool to characterize the molecular mechanism of multicomponent complex.